Peran Adat Alas dalam Perkembangan Kaum Muda di Aceh Tenggara - Reh Ulina Bintang; Muhammad Adika Nugraha; Abdul Azis (Polyscopia, 2024)
The role of Alas customs in Southeast Aceh's youth development is exemplified through the tradition of "mepahukh." This practice facilitates social connections and aids young individuals in finding suitable life partners. The Pemamanen tradition, deeply rooted in Aceh Tenggara and integral to the Alas ethnic group, holds historical and functional significance. Pemamanen is a crucial aspect of the Alas or Khang Alas tradition in Aceh Tenggara, reflecting its enduring presence in Alas society. The Islamic perspective on Pemamanen in Kutacane, Southeast Aceh, emphasizes Muslims' obligation to follow Prophet Muhammad's teachings and avoid practices conflicting with Islamic principles. Within Islamic jurisprudence, customary traditions, including life events like Pemamanen, require scrutiny to align with Islamic principles. Mepahukh, a tradition for young people, serves as an example, emphasizing the need for Islamic compatibility in customary practices.